Prevalence and Correlates of Anti‐Parkinson Drug Use in a Nationally Representative Sample - Dahodwala, Nabila (Mov Disord Clin Pract, 2016)
BACKGROUND: Although numerous prescription drugs are available to treat Parkinson's disease (PD), little is known about national use in clinical practice and which factors may influence variability in care. The objectives of this study were to describe the prevalence of anti‐Parkinson drug use among Medicare beneficiaries with PD and to identify demographic and clinical factors associated with drug use. METHODS: This retrospective study was based on a random sample of annual 5% Medicare Part A and B claims linked with Medicare Part D drug files from 2007 through 2010. The study sample included fee‐for‐service Medicare beneficiaries with continuous stand‐alone Part D enrollment who had been diagnosed with PD in the given year. First, any PD drug use and drug use by class (levodopa, dopamine agonist, anticholinerigc, monoamine oxidase B inhibitors, catechol‐O‐methyltransferase inhibitors, and amantadine) were described. Using generalized estimating equation regressions, patient and provider characteristics associated with anti‐Parkinson drug use and choice were examined. RESULTS: Over 81% of patients with PD were treated with anti‐Parkinson drugs, and this proportion was stable over the 4 years of the study. The majority were treated with levodopa (90%); followed by dopamine agonists (29–31%); then monoamine oxidase B inhibitors, anticholinergics, amantadine, and catechol‐O‐methyltransferase inhibitors (all between 5% and 11%). Holding all else equal, patients who were not seen by a neurologist (odds ratio, 0.41; 95% confidence interval, 0.38–0.44; P < 0.001) and African‐American patients (odds ratio, 0.80; 95% confidence interval, 0.69–0.93; P = 0.003) were significantly less likely to be treated. CONCLUSIONS: Among a national sample of Medicare beneficiaries with PD, the majority received anti‐Parkinson drugs. However, there was relative under‐treatment of African‐Americans and patients who were not seen by a neurologist for care.